GUT MICROBIOTA-ASSOCIATED IMMUNE MODULATION IN PATIENTS WITH ALLERGIC DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Allergic diseases represent a growing global health challenge, with increasing prevalence across both developed and developing countries. Recent advances in immunology and microbiology have highlighted the pivotal role of the gut microbiota in regulating host immune responses and maintaining immune homeostasis. This article examines the mechanisms through which gut microbiota modulates immune function in patients with allergic diseases. Particular attention is given to microbial diversity, early-life microbiota development, microbial metabolites, and host–microbe interactions influencing allergic sensitization and disease progression. By synthesizing current scientific evidence, this review emphasizes the potential of microbiota-targeted interventions as innovative strategies for the prevention and management of allergic disorders.